1980
DOI: 10.1016/0042-6822(80)90058-6
|View full text |Cite
|
Sign up to set email alerts
|

The coronavirus avian infectious bronchitis virus requires the cell nucleus and host transcriptional factors

Abstract: Replication of avian infectious bronchitis virus in permissive BHK-21 cells is blocked when these cells are enucleated or irradiated with ultraviolet light prior to infection, or if cells sre treated with a-amanitin during the virus growth cycle. This coronavirus, like influenza virus, can replicate normally in the presence of cr-amanitin in Chinese hamster ovary cells which possess a drug-resistant RNA polymerase II. These findings indicate that avian infectious bronchitis virus requires the intact cell nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…Table I shows that the replication of MHV-A59, MHV-JHM and VSV was not restricted in enucleated cells, in cells treated with ~-amanitin, or in cells treated with both ~-amanitin and actinomycin D. The moderate decrease in MHV-A59 replication in the enucleated cells was probably due to the disruption of cellular metabolism by cytochalasin B treatment, since a similar decrease was observed in mock-enucleated cells. Replication of VSV is known to be unaffected by these treatments; however, influenza virus replication is suppressed (Follett et al, 1974;Evans & Simpson, 1980). The data obtained in this study indicate that the host cell nucleus is not required for the synthesis of MHV.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Table I shows that the replication of MHV-A59, MHV-JHM and VSV was not restricted in enucleated cells, in cells treated with ~-amanitin, or in cells treated with both ~-amanitin and actinomycin D. The moderate decrease in MHV-A59 replication in the enucleated cells was probably due to the disruption of cellular metabolism by cytochalasin B treatment, since a similar decrease was observed in mock-enucleated cells. Replication of VSV is known to be unaffected by these treatments; however, influenza virus replication is suppressed (Follett et al, 1974;Evans & Simpson, 1980). The data obtained in this study indicate that the host cell nucleus is not required for the synthesis of MHV.…”
Section: Discussionsupporting
confidence: 64%
“…These data showing nuclear independence of MHV replication in L2 cells contrast with those obtained for coronavirus 229E in L132 cells and IBV in BHK-21 cells (Kennedy & Johnson-Lussenburg, 1979;Evans & Simpson, 1980). Although Evans & Simpson (1980) report that actinomycin D and ~-amanitin blocked the production of IBV, Stern & Kennedy (1980) observed no reduction in the recovery of infectious IBV from chicken embryo kidney cells incubated in the presence of 1/tg/ml actinomycin D. Unfortunately, we cannot resolve the difference between our data with MHV and those of Evans & Simpson (1980) obtained with IBV, as neither BHK-21 nor CHO ceils will support the growth ofMHV (S.A. Stohlman, unpublished results).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…There has been some debate on the requirement for the cell nucleus in coronavirus replication. Evans & Simpson (1980) demonstrated that avian infectious bronchitis virus replication was blocked in cells from which the nucleus had been removed or inactivated and suggested a requirement for transcriptional factors similar to those essential for influenza virus. Two other groups working with murine hepatitis virus, however, showed that the virus grew efficiently in enucleated cells (Brayton et al, 1981;Wilhelmsen et al, 1981).…”
mentioning
confidence: 99%